Introducing the Neuroplastic Narrative: a non-pathologizing biological foundation for trauma-informed and adverse childhood experience aware approaches - Peckham, Haley (Frontiers in Psychiatry, 2023)
Most people accessing mental health services have adverse childhood experiences (ACEs) and/or histories of complex trauma. In recognition of this, there are calls to move away from medical model approaches and move toward trauma-informed approaches which privilege the impact of life experience over underlying pathology in the etiology of emotional and psychological suffering. Trauma-informed approaches lack a biological narrative linking trauma and adversity to later suffering. In its absence, this suffering is diagnosed and treated as a mental illness. This study articulates the Neuroplastic Narrative, a neuroecological theory that fills this gap, conceptualizing emotional and psychological suffering as the cost of surviving and adapting to the impinging environments of trauma and adversity. The Neuroplastic Narrative privileges lived experience and recognizes that our experiences become embedded in our biology through evolved mechanisms that ultimately act to preserve survival in the service of reproduction. Neuroplasticity refers to the capacity of neural systems to adapt and change. Our many evolved neuroplastic mechanisms including epigenetics, neurogenesis, synaptic plasticity, and white matter plasticity allow us to learn from, and adapt to, past experiences. This learning and adaption in turn allows us to better anticipate and physiologically prepare for future experiences that (nature assumes) are likely to occur, based on past experiences. However, neuroplastic mechanisms cannot discriminate between experiences; they function to embed experience regardless of the quality of that experience, generating vicious or virtuous cycles of psychobiological anticipation, to help us survive or thrive in futures that resemble our privileged or traumatic pasts. The etiology of suffering that arises from this process is not a pathology (a healthy brain is a brain that can adapt to experience) but is the evolutionary cost of surviving traumatizing environments. Misidentifying this suffering as a pathology and responding with diagnosis and medication is not trauma-informed and may cause iatrogenic harm, in part through perpetuating stigma and exacerbating the shame which attends complex trauma and ACEs. As an alternative, this study introduces the Neuroplastic Narrative, which is situated within an evolutionary framework. The Neuroplastic Narrative complements both Life History and Attachment Theory and provides a non-pathologizing, biological foundation for trauma-informed and Adverse Childhood Experience aware approaches.